Hepatic resection for malignant liver tumours in the elderly: a systematic review and meta‐analysis. Issue 11 (15th June 2015) - Phan, Kevin; An, Vincent Vinh Gia; Ha, Hakeem; Phan, Steven; Lam, Vincent; Pleass, Henry
Abstract Background The number of elderly patients undergoing hepatic resection for surgical treatment of benign and malignant cancers is increasing. However, there is limited clinical data on the complications and long‐term survival rates associated with liver surgery in the elderly patients (≥70 years) versus younger patients for malignant liver conditions. Methods Six electronic databases were searched for original published studies comparing elderly (≥70) versus younger (<70) cohorts for malignant liver tumours. Data were extracted and analysed according to predefined clinical endpoints. Results Twenty‐seven comparative studies were identified, including 4769 elderly patients versus 15 855 younger patients (n = 20 624). There was significantly higher 30‐day mortality in the elderly colorectal liver metastasis group (P < 0.00002) and significant difference between elderly and young in terms of overall survival (hazard ration (HR), 1.10; P = 0.02). However, there was no difference in disease‐free survival (HR, 1.05; P = 0.27). Post‐operative pneumonia, renal failure and infection were more frequent in the elderly group. Conclusions Liver resection for malignant hepatic tumours in the elderly is associated with a greater 30‐day mortality and overall mortality when compared with younger cohorts, but similar disease‐free survival. Length of stay and transfusions were not significantly different while pneumonia, renal failure and infections were more frequent in the elderly group.